The Level of Knowledge, Attitudes, Behaviour of Women in Reproductive Age (WRA) with Online Class BSE - Hesti Kurniasih; Sumiyati Sumiyati; Septerina Purwandani Winarso; Fitria Zuhriyatun (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Breast cancer is the second leading cause of malignancy among women in Indonesia. Breast Self-Examination (BSE) is one way of early detection to determine the presence of a mass in the breast. But in reality, the awareness to do BSE is still lacking among women. This study aims to determine changes in the level of knowledge, attitudes, and behavior of women of childbearing age (WUS) after attending BSE online classes. This study uses a one-group pretest-posttest. The population in this study were women of childbearing age who came to the integrated service post. Subjects were selected using a purposive sampling technique according to the inclusion criteria of as many as 25 respondents. Based on the results of the research conducted, there are differences in scores before and after the online class on BSE. Before counseling the average score was 53.8 after counseling the average score was 63. The results of the bivariate analysis the average behavioral pretest score was 2.76 while the post-test average was 5.64 with a p-value of 0.01 0.005 so it was concluded that there was a significant difference in the average pretest and post-test behavior scores. The average pretest knowledge score is 17.48 while the post-test average score is 22.96 with a p-value of 0.01 0.005 there is a significant difference in the pretest and post-test knowledge scores. The pretest attitude score was 53.8 while the post-test score was 63 with a p-vale value of 0.01 0.005, indicating that there was a significant difference between the pretest and post-test attitude scores. This shows that online classes have a positive influence on WRA's behavior to do BSE. As a comparison tool for the world of science in enriching information about BSE behavior, it is necessary to conduct research using other methods that further explore the activity of respondents, for example through video media.